Potential impact of a Moraxella catarrhalis vaccine in COPD. Issue 37 (3rd September 2019) - Perez, Antonia C.; Murphy, Timothy F.
Abstract: Moraxella catarrhalis is the second most common cause of exacerbations in adults with COPD, resulting in enormous morbidity and mortality in this clinical setting. Vaccine development for M. catarrhalis has lagged behind the other two important causes of exacerbations in COPD, nontypeable Haemophilus influenzae and Streptococcus pneumoniae. While no licensed vaccine is currently available for M. catarrhalis, several promising candidate vaccine antigens have been identified and characterized and are close to entering clinical trials. Key steps that are required to advance vaccines for M. catarrhalis along the translational pipeline include standardization of assay systems to assess candidate antigens, identification of a reliable correlate of protection and expansion of partnerships between industry, academia and government to overcome regulatory hurdles . A vaccine to prevent M. catarrhalis infections in COPD would have a major impact in reducing morbidity, mortality and healthcare costs in COPD.